Management of Infertility due to Anovulation (Beejadusti Janya Stri Vandhyatwa) by Ayurvedic Regime - Suman Kumari; Hetal.H.Dave (AYUSHDHARA, 2024)
Anovulation is one among the major factors contributing to infertility in women. Anovulation occurs when an egg does not release or ovulate from woman’s ovaries. This issue worsens due to changing lifestyles, poor eating habits, stressful employment, and environmental factors. Ovulation induction and artificial reproductive techniques are the available treatment options for these patients. Ayurvedic formulations having properties like – Prajasthapana, anti-oxidant, Balya, Rasayana, Yonidoshahara, Tridhosha shamana shown improvement in infertility due to anovulation. The present case represent case study of a 31 year old female diagnosed as primary infertility visited OPD of National Institute of Ayurveda on 04.04.2024 with complaint of anxious to conceive since 11 years. On assessment of all report, anovulation was found to be the etiology. Treatment opted was Shaman Chikitsa with Bala Beeja Churna– 4gm BD after food with lukewarm water and Ashwagandha Ghrita 5ml BD before food with 100ml of milk. The patient got conceived after 2 months of oral medications, and UPT was found positive on 28 may, 2024.